Youtube Platform as an Innovation in Digital Learning in Efforts to Empower Islamic Families Based on The Values of The Qur'an - Nabil Latifa Mutiah Sukma; Triono Ali Mustofa; Rabi’atul’adawiyah Rabi’atul’adawiyah (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2025)
This study aims to examine the use of the YouTube platform as a digital learning innovation in an effort to empower Islamic families based on the values of the Qur'an and analyze the level of effectiveness and impact it has on Muslim families. This study uses a qualitative approach with a phenomenological design to understand the experiences and perceptions of audiences in accessing Islamic family education content through the YouTube platform. Data were obtained through semi-structured interviews and questionnaires with active YouTube audiences, and supported by literature studies and digital content analysis. The results of the study show that the YouTube platform functions not only as a da'wah medium, but also as a digital learning space that enables the process of internalizing the values of the Qur'an continuously in family life. The content is presented systematically, argumentatively and applicatively and there are YouTube features such as replays, playlists, comment columns and live streaming that encourage independent, flexible and participatory learning. The questionnaire findings show a very high level of acceptance of YouTube as a digital learning innovation, with all respondents feeling the benefits and positive changes in family life. So that the YouTube platform contributes to strengthening religious understanding, awareness of the role of the family and the resilience of Muslim families who are able to contribute to realizing efforts to empower Islamic families based on the values of the Qur'an.